Application of Fuzzy Infrence System Mamdani Method to Determine the Amount of Durian Pancake Production - Wira Apriani; Yuda Perwira (Jurnal Mantik, 2021)
UMKM is one of the drivers of the economy in the village so that its existence is very important and important to pay attention to so that it can still produce and employ people in rural areas. and on the part of the owner who has not applied technology to their business, one of which is the production plan, at this time the production plan is only based on estimates, so it often happens that there is too much stock left or until the sales stock runs out. The purpose of this study was to make a determination system of production with fuzzy logic in the hope this system can help SMEs pancake durian determine the number of correct production in order to minimize inventory items left or run out of inventory. The data material used is the supply of and demand for visits supply demand from the lowest to the medium and the highest so that the range can be concluded and processed using the Mamdani fuzzy method so that the calculation of the amount of production can be determined precisely.